Robotising Existing Astronomical Observatories - Tuparev, G.; Andreasyan, H. R.; Thomas M. Jackson
Astronomical observatories can be operated either manually or remotely, but both of these options currently have many disadvantages. Manual observatories require real-time staffing by on-site astronomers and technicians, and observation time is often not used optimally. Remote observatories, on the other hand, often make it cumbersome or near-impossible to modify any observing schedules already fed into the system, making reacting to important events like gamma-ray bursts unrealistic. In addition, it is generally expected that the cheapest way to upgrade an ageing observatory is to simply build a new one, but this is not always the case. For many relatively modern observatories, it is possible to convert to a fully robotic mode of operation. In these proceedings, we describe a few straightforward ways to robotise an existing observatory and how to connect it to a network of other robotic observatories. We also discuss the use of inexpensive device controllers, the importance of emergency shut-down procedures, the introduction of local and network schedulers, and the implementation of fully automated observation planning. We finally also describe hardware and software solutions, including an example of how this is currently being applied.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture